The Problems Faced by Students in Classroom Presentation - Riski Shafira; Bukhari Daud; Nurul Inayah (Research in English and Education Journal, 2019)
This study aimed at investigating the speaking problem faced by the students of English Education Department of Teacher Training and Education Faculty of Syiah Kuala University in conducting presentation. It was also intended to find out the factors that cause those problems in classroom presentation. A descriptive qualitative study was undertaken by handing out the questionnaire to 20 students of 2017 academic year and interviewing 6 of them in order to attain the needed data in this study. The respondents were chosen by using purposive sampling. The results from questionnaire showed that there were four problems that students’ faced in doing classroom presentation; those problems are the use of mother tongue, the lack of vocabulary, inhibited to speak in public, and lack of confidence. The result of interview revealed the factors that cause those problem are the students feel more comfortable if they mix the language, the lack of vocabulary that makes them hesitant to speak and have nothing to say, fear of making errors or mistakes and nervousness, and fear of being mocked by the other students.